Coagulation and endothelial dysfunction during longterm hyperdynamic porcine bacteremia – effects of selective inducible nitric oxide synthase inhibition - Matejovic, Martin; Krouzecky, Ales; Radej, Jaroslav; Rokyta, Richard Jr.; Kralova, Hana; Radermacher, Peter; Novak, Ivan (Thrombosis and Haemostasis, 2007)
Coagulation abnormalities have been implicated in the pathogenesis of sepsis and organ dysfunction. Nitric oxide (NO) is regarded as a critical mediator of many vascular pathologies, including sepsis. However, limited evidence is available to document a relationship between NO generated by inducible NO synthase (iNOS) and hemostatic abnormalities in sepsis. Therefore, we evaluated the effects of selective iNOS inhibition on markers of endothelial and coagulation homeostasis in a clinically relevant model of porcine bacteremia induced and maintained for 24 hours (h) with a continuous infusion of live P. aeruginosa. After 12 h of sepsis, animals received either vehicle (Control, n = 7) or continuous infusion of selective iNOS inhibitor L-NIL (n=7). Before as well as 12, 18 and 24 h after starting P. aeruginosafollowing variables related to i) endothelial dysfunction (von Willebrand factor [vWf]; tissue plasminogen activator activity [t-PA]; ii) coagulation (thrombin-antithrombin complexes [TAT]; platelet count); iii) fibrinolysis (t-PA activity, activity of plasminogen activator inhibitor type 1 (PAI-1 act); and iv) oxidative/ nitrosative stress (isoprostanes, nitrate/nitrite levels) were measured. L-NIL inhibited sepsis-induced increase in plasma nitrate/nitrite and isoprostanes concentrations, prevented hypotension and acidosis. L-NIL significantly attenuated sepsisinduced rise in plasma vWF and TAT. P. aeruginosa-induced drop in t-PA activity was blunted by iNOS inhibition, while increased PAI-1 and reduced platelet count were not reversed by the treatment. In conclusion, selective iNOS inhibition was associated with attenuation of sepsis-induced coagulation and endothelial dysfunction suggesting the interplay between mediators of vascular system and hemostatic balance. Reduction of oxidative stress probably contributes to the beneficial effects afforded by iNOS blockade.
Keywords: Coagulation; DIC; nitric oxide; oxidative stress; sepsis